Pengaruh Distribution Intensity Terhadap Customer Loyalty Melalui Brand Image, dan Perceived Quality Sebagai Variabel Intervening Pada Semen Tiga Roda di Surabaya - Augustinus Ivan Christian (Jurnal Strategi Pemasaran, 2016)
The national development is a way to make infrastructure growing faster. As we can see Surabaya have a national development like a highway construction from Mojokerto to Surabaya. Because of that make the use of cement in surabaya increased. Cement is a primary comodity to development. Many brand of cement making a competition beetween the brand cement in Surabaya. 1 option to win the competition is to make a good Distribution This research aim to analyze the effect of Distribution Intensity toward Customer Loyalty Cement Tiga Roda in Surabaya with Brand Image and Perceived Quality as intervening variable. This research will be conducted by distributing questionnaires to 100 respondents who use Cement with cement Tiga roda, Quantitative analysisi with path analysis were used for the technical analysis.